Organizational identification as perceived by merger and acquisition employees - Ismail, Maimunah; Umar Baki, Nordahlia; Omar, Zoharah; Bebenroth, Ralf (Universal Publishers, 2016)
This study examined the influence of two organizational factors, namely organizational justice and organizational culture factors on organizational identification following merger and acquisitions (M&A) in Malaysia. This correlational study used the Social Identity Theory as its underpinning theory. Data were obtained from 219 respondents and were analysed using structural equation modelling. It is shown that rather organizational culture than organizational justice factors influence significantly on organizational identification with 62% explanatory power. Specifically, developmental, rational and group cultures were the significant predictors of organizational identification. The study gives practical significance to human resource managers in strengthening organizational identification as perceived by employees after an M&A by considering the crucial role of organizational culture factors. This is among the earliest study conducted that jointly links organizational factors of justice and culture in the context of employees' post-merger integration. It theorises on human issues at M&A and enriches the Western literature on organizational identification by providing insights of firms in a South East Asian country. The research was limited in terms of respondents who were employed in M&A organizations in the Klang Valley area of Malaysia.